Knowledge and attitude about organ donation and transplantation among Omani university students - Alwahaibi, Nasar; Al Wahaibi, Anas; Al Abri, Mohammed (Frontiers in Public Health, 2023)
Background Despite the importance of organ donation and transplantation in improving the quality of life, still, there is a shortage of organ donations, worldwide. Lack of knowledge among the public could be the reason. In previous studies, the focus was predominantly on medical students at universities. The aim of this study was to assess university students’ knowledge and attitude about organ donation and transplantation among different colleges at the university. Method A cross-sectional study was conducted among university students between August 2021 and February 2022 using a validated self-designed questionnaire. The questionnaire consisted of five sections. The first section was about the research information. The second section was informed consent. The third section was about sociodemographic information. The fourth section was about the knowledge of organ donation. The last section was about the attitude toward organ donation. The data were analyzed by descriptive statistics and chi-square tests. Results The study included 2,125 students. 68.1% were females, and 93.1% were in the age group 17–24 years old. Only 34.1% had good knowledge about organ donation, 70.2% had a low attitude, and 7.53% had adequate information about brain death. The most common reason for supporting donating organs among university students was to save a life (76.8%) and the most common reason for refusing organs, was I am still unaware. In addition, only 25.66% of the participants had a high attitude toward people with poor knowledge about organ donation. The majority of the students (84.13%) used online sources and social networks as the primary sources of information about organ donation. Conclusion The knowledge and attitudes of university students toward organ donation and transplantation were low. Saving a life was the most common reason for supporting organ donation, and knowledge was the biggest obstacle. Online sources and social networks were the primary sources of knowledge. The attitude was greatly influenced by knowledge. Organizing campaigns, and events, and incorporating organ donation and transplantation into university curricula will increase university students’ knowledge and attitudes.